Combination MET inhibition and Topoisomerase I inhibition block cell growth of Small Cell Lung Cancer - Rolle, Cleo E. (Mol Cancer Ther, 2013)
Small cell lung cancer (SCLC) is a devastating disease, and current therapies have not greatly improved the 5-year survival rates. Topoisomerase (Top) inhibition is a treatment modality for SCLC; however, the response is short lived. Consequently, our research has focused on improving SCLC therapeutics through the identification of novel targets. Previously, we identified MNNG HOS transforming gene (MET) to be overexpressed and functional in SCLC. Herein, we investigated the therapeutic potential of combinatorial targeting of MET using SU11274 and Top1 using 7-ethyl-10-hydroxycamptothecin (SN-38). MET and TOP1 gene copy numbers and protein expression were determined in 29 patients with limited (n = 11) and extensive (n = 18) disease. MET gene copy number was significantly increased (>6 copies) in extensive disease compared with limited disease (P = 0.015). Similar TOP1 gene copy numbers were detected in limited and extensive disease. Immunohistochemical staining revealed a significantly higher Top1 nuclear expression in extensive (0.93) versus limited (0.15) disease (P = 0.04). Interestingly, a significant positive correlation was detected between MET gene copy number and Top1 nuclear expression (r = 0.5). In vitro stimulation of H82 cells revealed hepatocyte growth factor (HGF)–induced nuclear colocalization of p-MET and Top1. Furthermore, activation of the HGF/MET axis enhanced Top1 activity, which was abrogated by SU11274. Combination of SN-38 with SU11274 dramatically decreased SCLC growth as compared with either drug alone. Collectively, these findings suggest that the combinatorial inhibition of MET and Top1 is a potentially efficacious treatment strategy for SCLC.